(untitled) (Journal of Plant Disease Sciences, 2025)
This study investigates the biocontrol potential and plant growth promoting abilities of five isolates of (Ma1 to Ma 5) against ,Exserohilum turcicum the causative agent of maize leaf blight. Among the isolates, Ma2 demonstrated the highest antagonistic activity, achieving 84.66% growth inhibition of , indicating its potential as a biocontrol agent. The study also evaluated plant growth promoting traits of , including iron chelation through siderophore production, phosphate solubilization, indole-3- acetic acid (IAA) synthesis and ammonia production, with Ma2 excelling in these areas. Notably, Ma2 showed 70.45% siderophore activity, 57.80% phosphate solubilization efficiency and IAA production of 49.65 μg/ml. Overall, this study highlights Ma2 as a dual function agent, effective against and as a promoter of plant growth of maize.